Le parti communiste de Belgique (1921-1944) : actes de la journée d'étude de Bruxelles, 28 avril 1979 - Blume, Marianne; Dupont, Christian; Heirwegh, Jean-Jacques; Gotovitch, José; Van Doorslaer, Rudi (Bruxelles: Fondation Joseph Jacquemotte, 1980)
"Marianne Blume, Christian Dupont, Jean-Jacques Heirwegh, ... et al. ; rédaction finale: José Gotovitch et Rudi Van Doorslaer Bibliotheek François VercammenArchief Rudi Van Doorslaer"